2004
DOI: 10.1007/s10404-004-0006-7
|View full text |Cite
|
Sign up to set email alerts
|

Transient performance of flow over a rotating object placed eccentrically inside a microchannel?numerical study

Abstract: Industrial applications today are demanding the implementation of microelectromechanical systems (MEMS) into their products. These are mechanical devices that are able to perform work, and yet have characteristic lengths less than 1 mm. As a result, the Reynolds number is typically low, which indicates the dominance of viscous forces. When a cylinder is placed eccentrically inside a microchannel, where the rotor axis is perpendicular to the channel axis, a net force is transferred to the fluid as a result of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…These rotors could become noncircular as a result of these imperfections in manufacturing. Also, future micropumps may not even utilize rotors with circular cross sections, as is the case for the cellular motor-based micropump, which is currently in development for future use as a novel drug delivery system, and which utilizes a capsule-shaped rotor [6]. Accordingly, there is serious need to study the fluid dynamic transport around a spinning square which is yet to be reported in the contemporary literatures.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These rotors could become noncircular as a result of these imperfections in manufacturing. Also, future micropumps may not even utilize rotors with circular cross sections, as is the case for the cellular motor-based micropump, which is currently in development for future use as a novel drug delivery system, and which utilizes a capsule-shaped rotor [6]. Accordingly, there is serious need to study the fluid dynamic transport around a spinning square which is yet to be reported in the contemporary literatures.…”
Section: Introductionmentioning
confidence: 96%
“…However, similar studies on rotating square cylinder are almost unavailable. Few studies are available for the flow past a square cylinder with an angle of incidence [18,19] and few demonstrate the performances of various rotating objects placed inside a microchannel [6] or within a square [20] and/or circular enclosures [21]. Accordingly, we aim here to numerically investigate the fluid dynamic transport around a rotating square cylinder in a free 1 stream.…”
Section: Introductionmentioning
confidence: 99%
“…The simplicity in the design of the viscous pump is its major attractive feature for MEMS, NEMS and LOC applications. The viscous pump consists of a transverse-axial rotor (usually cylindrical, but not always as in the numerical study of Phutthavong and Hassan (2004)) eccentrically placed in a channel, so that the viscous resistance between the small and large gaps between the cylinder and the channel walls generate a net flow along the channel. The advantages of such a viscous pump extend beyond MEMS, NEMS and LOC devices, as they may be utilized for medical or biological purposes since they are capable of pumping very small flowrates of fluid, which is necessary in applications such as drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The design of the rotating gutter is illustrated in the block diagram where the structure of the rotating tube is represented as a spherical turbine in which the division of the spherical turbine into slides affects the rotation significantly [22,23].…”
Section: 2 Design Of Rotating Turbinementioning
confidence: 99%